3D Ni(II)/Cu(II) Supermolecular Frameworks Based on Pyridylamine and Fumarate Co‐ligands Containing a Trinodal (4, 5, 6)‐Connected Network and a (H2O)16 Water Cluster. Issue 2 (8th January 2013) - Kang, Yifan; Liu, Qing; Yin, Wenting; Zhang, Wentao; Liu, Ping
Abstract Two new complexes, [Ni(dpypda)(H2O)3]·(fum) (1) and [Cu2(dpypda)2(fum)2]n·8nH2O (2) (dpypda=N2, N4‐di(pyridin‐2‐yl)pyrimidine‐2, 4‐diamine, fum=fumarate), have been synthesized and characterized by single‐crystal X‐ray diffraction. Complex 1 is a discrete unit, exhibiting a (4, 5, 6)‐connected framework formed by hydrogen bonding interactions and electrostatic interactions between free fum dianions and mononuclear [Ni(dpypda)(H2O)3]2+ cations. However, in complex 2, two crystallographically independent fum dianions adopt the alternative mode of mixed monodentate bridging and chelating and bis(monodentate) bridging Cu(II) atoms to produce a one‐dimensional (1D) in?nite zigzag chain. And there are unique (H2O)16 water clusters which consist of one cyclic (H2O)4 tetramer and two cyclic (H2O)5 pentamer with six dangling water molecules in its 3D supramolecular framework. Both 1 and 2 are characterized by IR and elemental analysis, and the TG properties were also investigated for 2.